PAPER GRADING–AN ACCOUNTING INSTRUCTOR'S DILEMMA. - Moss, Kermit C. (The Accounting Review, 1957)
An accounting instructor's work is comparable to that of the football coach. The coach can teach his players the theory of football and get them to understand his diagrams but unless he conducts regular scrimmages, he will never develop a football team. The scrimmage for a student of accounting consists of the assigned problems, the workbook and the practice set. So it seems that it would be desirable for the student to work several problems in connection with each chapter. Apparently many instructors fail to face up to the situation. They recognize the desirability of the scrimmaging, but have found no satisfactory way to handle the grading problem. Often the instructor at least implies that the paper are being graded, but the students suspect that they are not. In a situation where objective tests are effective and in certain types of problem tests much time can be saved by having the students grade their own papers. It seems desirable to go over the test thoroughly with the students at the next class meeting anyway, so then is no loss of classroom time if the students grade their own papers.